Association between the level of indifference to dental treatment and habits of oral hygiene in adults - Callalli, Luis (2022)
Introduction: Inadequate oral hygiene habits such as lack of tooth brushing, use of irrigators, fluoridated toothpastes, and dental floss, as well as the importance of worrying about going to the dentist in the event of any problem in the oral cavity and the continuity of treatment are factors that could increase the risk in patients. Objetive: To determine the association between the level of indif ference to dental treatment and the oral hygiene habits of those surveyed adults. Material and Methods: An observational, analytical and cross-sectional study. The level of indif ference to dental treatment was evaluated using a translated virtual questionnaire and subsequently internally validated (Cronbach's alpha: 0.91). There were a total of 249 participants, 150 males and 99 females with a mean age of 30.69 years. For the association of the qualitative variables and the report of the crude and adjusted odds ratio (OR), a logistic regression was used. We worked with a level of statistical significance of p<0.05 and a confidence interval of 95%. Results: A high level of indif ference to dental treatment was obtained in 57.83% of the respondents. Likewise, a statistically significant association was found between indif ference to dental treatment and education (p = 0.012). Regarding oral hygiene habits, a statistically significant association was found with flossing (OR = 2.22; 95% CI: 1.10-4.46) (p = 0.025) and brushing before sleeping (OR = 5.26; 95%: 2.26-12-22) p<0.001). Conclusion: There is a statistically significant association between the level of indif ference to dental treatment with oral hygiene habits, flossing and brushing before sleeping. It is advisable to carry out activities in the communities to promote oral health care to reduce levels of indif ference to dental treatment.